Transforming Global Information and Communication Markets - Peter F. Cowhey, Jonathan D. Aronson dan Donald Abelson (The MIT Press, 2012)
As 2009 nears, the world is in a time of gloom and panic. Will global governance and the global economic order survive? In retrospect, some saw the collapse of the dot com bubble as a portent of the fi nancial meltdown and the collapse of confi dence in the future. In the United States there is a dour bipartisan consensus that escalating special interest politics, budget defi cits, economic insecurity in the midst of more consumption, environmental and energy policy gridlock, and deep uncertainties about nationalsecurity strategy point to intractable problems in the design and conduct of public policy. In other countries the specifi c bill of complaints may differ, but a similar uneasiness is widespread. Although we can gripe as well as anyone about the worldâ€™s follies, this book is more upbeat. Since World War II, a planet-straddling information and communications technology (ICT) infrastructure has created a global information economy at an ever-accelerating pace. A radically different model for competition and public policy for this infrastructure was introduced that is far sounder than its predecessor. More remarkably, countries agreed to rewrite the basic international agreements governing commerce for the communications and information infrastructure in a way that makes more sense than the consensus that was forged immediately after 1945. For once, the transformation in governance and technology is not just a tale of the prosperous states doing better. These changes boosted the economic takeoff of India and China and other emerging powers, and also brought a much greater level of digital connectivity to the poor than anyone dreamed of in the late 1980s. Much remains to be done in poor countries, but an expanding record of successes now exists. For example, banking done over mobile phones (â€œm-bankingâ€) is taking off faster in developing countries, which lack well-developed fi nancial markets, than in wealthy countries